Children's literature review. Volume 168 - Krstovic, Jelena O.; Gale Group (Detroit Gale, 2012)
Presents full-text literary criticism on writers and illustrators for children and young adults. Critical essays are selected from leading sources, including published journals, magazines, books, monographs, reviews, and scholarly papers.
"Excerpts from reviews, criticism, and commentary on books for children and young people."
Electronic reproduction.
Keywords: Children's literature -- History and criticism; Children's literature -- Book reviews; Electronic books